Mechanochemical synthesis and pressureless sintering of TiB2-AlN composites - Kim, HJ; Choi, HJ; Lee, JG (AMER CERAMIC SOC, 2002)
TiB2-AlN composites have been fabricated by the pressureless sintering of a mechanochemically processed Ti, Al, and BN powder mixture. TiB2-AlN powder was obtained from the mixture of Ti, Al, and BN, which had a composition corresponding to 45.7 wt% TiB2-54.3 wt% AlN, after mechanochemical processing for longer than 24 h. X-ray diffraction and transmission electron microscopy analysis showed that the powder subjected to mechanochemical processing for 60 h consisted of crystallites less than 300 run in size with a disordered crystal structure. TiB2-AlN composites with 95% relative density, a flexural strength of 172 MPa, a fracture toughness of 4.6 MPa(.)m(1/2), a hardness of 12.0 GPa, and an electrical resistivity of 1488 muOmega(.)cm were obtained by pressureless sintering at 1700degreesC for 2 h of the powder subjected to mechanochemical processing for 60 h.
Keywords: MECHANICAL-PROPERTIES; MICROSTRUCTURE; DENSIFICATION; CERAMICS